Harnessing Event Sensory Data for Error Pattern Prediction in Vehicles: A Language Model Approach - Math, Hugo; Lienhart, Rainer; Schön, Robin (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
In this paper, we draw an analogy between processing natural languages and processing multivariate event streams from vehicles in order to predict when and what error pattern is most likely to occur in the future for a given car. Our approach leverages the temporal dynamics and contextual relationships of our event data from a fleet of cars. Event data is composed of discrete values of error codes as well as continuous values such as time and mileage. Modelled by two causal Transformers, we can anticipate vehicle failures and malfunctions before they happen. Thus, we introduce CarFormer, a Transformer model trained via a new self-supervised learning strategy, and EPredictor, an autoregressive Transformer decoder model capable of predicting when and what error pattern will most likely occur after some error code apparition. Despite the challenges of high cardinality of event types, their unbalanced frequency of appearance and limited labelled data, our experimental results demonstrate the excellent predictive ability of our novel model. Specifically, with sequences of 160 error codes on average, our model is able with only half of the error codes to achieve 80% F1 score for predicting what error pattern will occur and achieves an average absolute error of 58.4 ± 13.2h when forecasting the time of occurrence, thus enabling confident predictive maintenance and enhancing vehicle safety.